Language Acquisition in Children Aged 3-5 Years in Lubuk ‎Lintang Village, Seluma Regency: A Phonological Study - Pita Lestari; Agung Pribowo (JPI: Jurnal Pustaka Indonesia, 2023)
The study aims to examine the language acquisition process in children aged 3-5 years and to identify the factors influencing their language development in Lubuk Lintang Village, Seluma Regency. Employing a qualitative approach with descriptive methods, this research gathered data from conversations involving children and their surrounding environment, focusing on phonological studies. The subjects of the research were children aged 3-5 years and their parents or caregivers in Lubuk Lintang Village. Data collection techniques included observation (listening, recording, and note-taking), interviews, and documentation, with triangulation applied to ensure data validity. The data analysis followed a structured process, incorporating data reduction, data presentation, and conclusion drawing. The findings indicate that, in terms of phonological development, children had successfully acquired several vowel sounds [a], [e], [o], [i], [u], as well as a variety of consonant sounds, such as [b], [c], [d], [f], [g], [h], [j], [k], [l], [m], [n], [p], [q], [r], [s], [t], [v], [w], [x], [y], and [z]. Although some sounds had not yet been fully articulated in everyday speech, the children were in the process of acquiring these sounds. The primary factors influencing language acquisition were family and environmental influences, both of which significantly shaped the children's language development.